2006
DOI: 10.1111/j.1475-6773.2006.00546.x
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the Use of Postacute Care during the Initial Medicare Payment Reforms

Abstract: Objective. To examine changes in postacute care (PAC) use during the initial Medicare payment reforms enacted by the Balanced Budget Act of 1997. Data Sources. We used claims data from the 5 percent Medicare beneficiary sample in 1996, 1998, and 2000. Linked data from the Denominator file, Provider of Service file, and Area Resource File provided additional patient, hospital, and market-area characteristics. Study Design. Six disease groups with high PAC use were selected for analysis. We used multinomial logi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
13
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 18 publications
1
13
0
Order By: Relevance
“…However, this "interchangeability" concept remains controversial. Previous studies utilizing Medicare administrative data have supported the idea of interchangeability by noting that the choice of post-acute care service type depends more on region, availability and reimbursement form than on other factors (Buntin, Garten, Paddock, Saliba, Totten & Escarce, 2005, Kane, Lin & Blewett, 2002, Lin, Kane, Mehr, Madsen & Petroski, 2006. However, a number of stroke specific studies have found inpatient rehabilitation to result in superior patient outcomes when compared to other post-acute care settings (Deutsch, Granger, Heinemann, Fiedler, DeJong, Kane, Ottenbacher, Naughton & Trevisan, 2006, Kind, et al, 2006, Kramer, Steiner, Schlenker, Eilertsen, Hrincevich, Tropea, Ahmad & Eckhoff, 1997.…”
Section: Discussionmentioning
confidence: 92%
“…However, this "interchangeability" concept remains controversial. Previous studies utilizing Medicare administrative data have supported the idea of interchangeability by noting that the choice of post-acute care service type depends more on region, availability and reimbursement form than on other factors (Buntin, Garten, Paddock, Saliba, Totten & Escarce, 2005, Kane, Lin & Blewett, 2002, Lin, Kane, Mehr, Madsen & Petroski, 2006. However, a number of stroke specific studies have found inpatient rehabilitation to result in superior patient outcomes when compared to other post-acute care settings (Deutsch, Granger, Heinemann, Fiedler, DeJong, Kane, Ottenbacher, Naughton & Trevisan, 2006, Kind, et al, 2006, Kramer, Steiner, Schlenker, Eilertsen, Hrincevich, Tropea, Ahmad & Eckhoff, 1997.…”
Section: Discussionmentioning
confidence: 92%
“…Since discharges to skilled nursing facilities initially decreased in Medicare patients in response to payment reforms, it is possible that PAC facilities have increasingly attracted other payors to supplement revenue, and this would have important implications for national policy and health care reform. Prior analyses were also limited to Medicare patients with selected diagnoses, 5,11 and we sought to extend these analyses by evaluating trends in other age groups and in other diagnostic groups. Nationally-representative trends in patients being discharged to PAC facilities after discharge may also provide normative data to providers and hospital systems for comparison with their local discharge practices.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies demonstrated important shifts in the use of one type of post-acute care (home health, skilled nursing, or inpatient rehabilitation) to another in response to payment reforms, suggesting that for many patients one type of PAC was substituted for another. 5,11 However, substitution of skilled nursing or inpatient rehabilitation care for inpatient hospital care has not been examined. We hypothesize that diagnostic groups in which hospital length of stay is decreasing most would be accompanied by the greatest increases in discharges to PAC facilities.…”
Section: Introductionmentioning
confidence: 99%
“…1 Then, during the late 1990s and early 2000s, the introduction of a prospective payment system (PPS) and other Medicare postacute care payment reforms resulted first in an increased use of Medicare-paid skilled nursing facility (SNF) care and then a decreased use of this care. 2,3 Provision of postacute care in nursing homes has not been well documented, especially in recent years. It also remains unclear whether nursing homes have increased staff-to-resident ratios to meet the escalating needs of postacute patients.…”
mentioning
confidence: 99%